"Winning the women's world cup": gender, branding, and the Australia/New Zealand As One 2023 social media strategy for the FIFA Women's World Cup 2023™. Issue 4 (21st March 2022) - Beissel, Adam; Postlethwaite, Verity; Grainger, Andrew
Abstract: In this article we critically explore the social media strategy of the successful Australia-New Zealand 'As One' joint bid for the FIFA Women's World Cup 2023™. We explore how the As One bid harnessed Twitter to communicate a hosting vision that appealed to multiple audiences while strategically, and successfully, resonating with contemporary FIFA politics. We adopt quantitative and qualitative content analysis methods to develop the constructed presence and narrative patterns from the As One bid's Twitter activity. Our findings suggest content relied on two primary 'legacy' narratives which both conformed to current FIFA strategy and broader social and regional politics: growing football participation among women and girls and strengthening cultural, economic, and political relations in the Asia-Pacific. Ultimately, we argue the use of Twitter was strategic and targeted, deliberately appropriating popular FIFA narratives to build an emotive 'legacy' vision to gain support from voting members of the FIFA Council.